Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.7759/cureus.36362
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Perceptions and Practices Toward Eye Injuries First Aid Among General Population in the Western Region of Saudi Arabia: A Cross-Sectional Study

Abstract: The eye is a vital and extraordinarily perceptive part of the human body. A wide spectrum of possible outcomes from eye injuries, from temporary vision loss to permanent blindness. There is a lack of information about how to handle an eye injury. Education and raising awareness are the best way to prevent severe complications and eventual loss of vision. Therefore, the purpose of this study is to evaluate and assess general population knowledge and first aid practices regarding eye injuries in the Western Regi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
0
0
Order By: Relevance
“…However, other studies have reported variations in knowledge levels. Alhothali et al conducted a study and reported a higher overall knowledge score compared to the present study [19]. These differences could be attributed to variations in the study populations, geographical regions, or educational programs implemented to enhance eye injury awareness in specific contexts.…”
Section: Discussioncontrasting
confidence: 58%
“…However, other studies have reported variations in knowledge levels. Alhothali et al conducted a study and reported a higher overall knowledge score compared to the present study [19]. These differences could be attributed to variations in the study populations, geographical regions, or educational programs implemented to enhance eye injury awareness in specific contexts.…”
Section: Discussioncontrasting
confidence: 58%
“…Also, good knowledge was shown by the female gender. In the current study, a statistically significant association was found between age and awareness (P-value < 0.00001) [ 16 ]. However, it's important to clarify that these findings do not inherently imply that being female directly causes or affects knowledge.…”
Section: Discussionmentioning
confidence: 75%